Mediating effects of depression on anxiety and leisure constraints in patients with breast cancer - Hsiu-Mei Huang; Jun-Hung Lai; Tsai-Wei Huang (BMC Women's Health, 2019)
Abstract Background Patients with breast cancer often exhibit high levels of anxiety and depression and a considerable decrease in their ability to participate in leisure activities, which result in the long-term disruption of their daily lives. This study intended to explore the relationships among anxiety, leisure constraints, and depression and evaluate whether depression mediates the effects of anxiety on leisure constraints in patients with breast cancer. Method This prospective study included 106 patients with breast cancer. All the patients completed the Taiwanese version of the Hospital Anxiety and Depression Scale and Leisure constraints questionnaire. Path analysis was used to test the mediating role of depression. Results Leisure constraints, anxiety, and depression were positively interrelated and co-occurred in the patients. The accelerated bootstrapping confidence intervals of the indirect effect did not include zero (0.276–1.663). Moreover, depression completely mediated the effects of anxiety on leisure constraints in patients with earlier cancer stages but not in patients with advanced cancer stages. Conclusions Depression is a crucial mechanism underlying the relationship between anxiety and leisure constraints in patients with breast cancer. Although many patients experience minimal disruption of activities and roles during survivorship, they are unable to perform functional activities and satisfactorily play their roles. This is the first study to explore leisure constraints in patients with breast cancer and investigate the mediating role of depression that underlies the relationship between anxiety and leisure constraints. The current findings are clinically crucial because they suggest the need to consider the simultaneous management of anxiety and depression for alleviating leisure constraints.